Who coaches the coaches? Exploring the biographies of novice athletics coach education tutors - Stephens, D.; Stodter, A.; Timmis, M. (International Sport Coaching Journal, 2025)
Despite coach education being a focus of academic inquiry for over 20 years, coach developers (e.g., tutors) have been neglected from the literature until recently. In recognizing and understanding the role of the tutor in delivering quality learning programs for sport coaches, it is also important to consider who tutors are and how biographical factors influence their development toward expertise. This article utilizes Grenier and Kehrhahn`s Model of Expertise Redevelopment as a tool to aid understanding of the transition from sport coaching to tutoring. Narrative interviews were used with seven novice athletics coach education tutors embarking on a "fast-track" tutor development program. Data were subject to narrative thematic analysis and presented as composite vignettes. The vignettes portray six common themes highlighting that becoming a coach education tutor is a lifelong process of episodic experiences. The features of novice tutors` biographies are a useful starting point in evidencing the development of expertise. These findings could be used to inform tutor recruitment and training. The current study adds to the emerging body of literature by providing one of the first empirical accounts exploring the developmental experiences of novice coach education tutors.